MAURICE BLONDEL’S DIAGNOSIS OF EXTRINSICIST “MONOPHORISM": AN ENDURING CRITIQUE OF CHRISTIAN INTEGRALISM - Bernardi, Peter James (Pensando - Revista de Filosofia, 2023)
In the early decades of the twentieth century French Catholics were sharply divided over what strategy the Church should adopt to re-Christianize society. Under the pseudonym “Testis,” Maurice Blondel sharply criticized a Catholic alliance with the proto-fascist, nationalist movement of Action Francaise, whose leader was the notorious unbeliever Charles Maurras. This alliance had received a qualified endorsement in a series of articles published by the French Jesuit Pedro Descoqs. In contrast, Blondel defended the Catholic social democrats who sought social justice for the workers. Applying his philosophy of action, Blondel criticized the Catholics Maurrassians on three fundamental grounds, especially their extrinsicist [“monophorist”] understanding of the nature-grace relationship. Balthasar considered Blondel’s "Testis" essays to be "the most penetrating analysis of [what is called] Catholic integralism [intégrisme] that . . . represents an ever recurrent temptation for militant Catholics." Blondel’s diagnosis of this integralist mentality was also evoked by Yves Congar, O.P., at the close of the Second Vatican Council: "If one had to characterize in a word the Council’s approach, I would appeal to the ideal of knowledge that Maurice Blondel proposed and that he defended against what he termed rather strangely ’monophorism’, that is a reified conception of knowing.” Given the contemporary resurgence of Christian nationalist movements, Blondel’s diagnosis has lost none of its relevance.